2016
DOI: 10.1002/jmri.25562
|View full text |Cite
|
Sign up to set email alerts
|

Radiomic features for prostate cancer detection on MRI differ between the transition and peripheral zones: Preliminary findings from a multi‐institutional study

Abstract: Purpose To evaluate in a multi-institutional study whether radiomic features useful for prostate cancer (PCa) detection from 3 Tesla (T) multi-parametric MRI (mpMRI) in the transition zone (TZ) differ from those in the peripheral zone (PZ). Materials and Methods 3T mpMRI, including T2-weighted (T2w), apparent diffusion coefficient (ADC) maps, and dynamic contrast-enhanced MRI (DCE-MRI), were retrospectively obtained from 80 patients at three institutions. This study was approved by the institutional review b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
119
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 122 publications
(127 citation statements)
references
References 36 publications
5
119
0
Order By: Relevance
“…Quantitative ADC and texture features have previously been investigated and found to be significant for diagnosis of cancer using logistic regression and machine-learning models in both the PZ and TZ. [36][37][38][39] Among features studied, mean ADC, skewness, and entropy were all among the reported significant discriminatory features that could differentiate between clinically significant and low-risk (Gleason score = 6) cancers, as well as between Gleason score 3 + 4 vs. Gleason score 4 + 3 tumors using SVM and other machine-learning models. 36,37 Li et al reported AUC values using an initial set of features compared with the best performing subset/technique varying between 0.97 (CI 0.94-0.99) and 0.91 (CI 0.85-0.95) evaluating strictly TZ abnormalities, 36 while Fehr et al reported AUC values between 0.60 and 0.99 (CIs not provided) evaluating the TZ and PZ together.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Quantitative ADC and texture features have previously been investigated and found to be significant for diagnosis of cancer using logistic regression and machine-learning models in both the PZ and TZ. [36][37][38][39] Among features studied, mean ADC, skewness, and entropy were all among the reported significant discriminatory features that could differentiate between clinically significant and low-risk (Gleason score = 6) cancers, as well as between Gleason score 3 + 4 vs. Gleason score 4 + 3 tumors using SVM and other machine-learning models. 36,37 Li et al reported AUC values using an initial set of features compared with the best performing subset/technique varying between 0.97 (CI 0.94-0.99) and 0.91 (CI 0.85-0.95) evaluating strictly TZ abnormalities, 36 while Fehr et al reported AUC values between 0.60 and 0.99 (CIs not provided) evaluating the TZ and PZ together.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative ADC and texture features have previously been investigated and found to be significant for diagnosis of cancer using logistic regression and machine‐learning models in both the PZ and TZ . Among features studied, mean ADC, skewness, and entropy were all among the reported significant discriminatory features that could differentiate between clinically significant and low‐risk (Gleason score = 6) cancers, as well as between Gleason score 3 + 4 vs. Gleason score 4 + 3 tumors using SVM and other machine‐learning models .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, radiomics workflow contains five steps; data selection, medical imaging, feature extraction, exploratory analysis, and modeling . Compared with classic methods, radiomics is performed based on advanced pattern recognition tools and involves the extraction of a large number of quantitative features from digital images to determine relationships between such features and the underlying pathophysiology, which has been widely used in many fields, especially in cancer . However, most studies focused on differentiating two kinds of tumors and seldom on triple classification.…”
mentioning
confidence: 99%
“…Consequently, quantifying the spatial heterogeneity in vascularization of the whole tumor volume from DCE‐MRI data may be more informative and realistic. In that sense, radiomics approaches on DCE‐MRI have recently shown encouraging results, alone or with other MRI sequences, in order to improve the detection of prostate cancer, to distinguish benign and malignant adnexal masses, to identify relevant molecular subtypes of breast cancers, to detect lymph node metastases in breast cancers, or to predict response to neoadjuvant treatment for rectum, breast, and nasopharyngeal cancers . Soft‐tissue sarcomas (STS) are malignant mesenchymal tumors with important inter‐ and intratumoral heterogeneity known to be associated with high grade .…”
mentioning
confidence: 99%